The Second Amendment on Trial - Saul Cornell, Nathan Kozuskanich (University of Massachusetts Press, 2013)
On the final day of its 2008 term, a sharply divided U.S. Supreme Court issued a five-to-four decision in District of Columbia v. Heller.1 The high court struck down the District of Columbiaâ€™s stringent gun control laws as a violation of the Second Amendment, reversing almost seventy years of settled precedent that linked the meaning of the â€œright of the people to keep and bear armsâ€ with the preservation of a â€œwell regulated militia.â€2 Reinterpreting the meaning of the amendment as securing an individual right to own a gun in the home for the purpose of self-defense, the Court opened up a new chapter in the contentious history of gun rights and gun control. The Courtâ€™s decision had been eagerly anticipated, and from the outset the case had a dramatic quality. Heller was born from Parker v. District of Columbia, a case that began in 2003 with a lawsuit in which Dick Anthony Heller was one of six plaintiffs to challenge the District of Columbiaâ€™s gun laws (requiring all guns to be registered, but forbidding the registration of handguns) on Second Amendment grounds.3 The District of Columbia appealed to precedent and sought to have the case dismissed because the Second Amendment protected only a collective right related to the militia. The plaintiffs then filed a motion for summary judgment. The National Rifle Association (NRA)opposed pressing Parker as a test case and tried to have it joined with its own recently filed gun litigation, Seegars v. Ashcroft.4 The request was denied, and Hellerâ€™s lawyers, a group of libertarians connected to the Cato Institute and the Institute for Justice, pushed forward. The team emulated civil rightsâ€“era legal strategy by looking for sympathetic clients who would play well before the Court and in the public eye. Heller, a District of Columbia Special Police Officer who could not legally have a gun at home but who was able to carry a firearm at his job at the Thurgood Marshall Federal Judicial Center, provided them the vehicle to bring their historic challenge to the Districtâ€™s law.